Metabolic syndrome severity scoring using confirmatory factor analysis in Jordanian adults - Abu-Shaweesh, Ala’a; Alkhatib, Buthaina; Agraib, Lana M. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Metabolic syndrome (MetS) is a significant health concern with specified diagnostic criteria. Determining the severity of MetS and screening individuals with pre-MetS pose challenges. MetS severity score (MetSSS) is a new assessment method developed to better manage and diagnose MetS. The study aimed to design a MetS severity score (MetSSS) equation specific to Jordanian adults based on sex and age.Methods: 428 participants were recruited for MetSSS calculations in this cross-sectional study. A confirmatory factor analysis (CFA) of a single MetS factor allowed differential loadings across groups to generate sex- and age-specific, continuous MetSSS was performed. Results: Systolic blood pressure (SBP) exhibited the highest factor loading contributing factors in MetSSS, followed by high-density lipoprotein (HDL). In contrast, fasting blood glucose (FBG) and triglycerides (TG) had the lowest factor loadings across the MetS components for the total population. Results showed a strongly positive correlation between MetSSS and body mass index (BMI) (r=0.617, p